New method estimate diesel engine oil viscosity:Acoustic Emission Viscosity (AEvisco) - Othman I.; Nordin J.; Jailani M. M. N.; Fauziah, Mat (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.